Co-axial silicon/perovskite heterojunction arrays for high-performance direct-conversion pixelated X-ray detectors - Tian, Shukai; Sui, Fan; He, Ke; Cheng, Guanming; Ge, Yongshuai; Ning, De; Wang, Zhongguo; Wang, Zhixun; Tao, Guangming; Wang, Zongpeng; Du, Bi; Wei, Lei; et al. (Nano energy, 2020)
Creating monolithic silicon/perovskite structures is a promising approach to engage emerging perovskite materials with silicon circuitry, which is essential to achieve industry-scale applications such as high performance X-ray detection. In particular, to achieve pixelated perovskite is a key step to address the issue of electrical crosstalk and low spatial resolution in imaging caused by inefficient migration and collection of carriers in the direction of signal collection. However, with the existing top-down methods, the thickness of patterned perovskite is limited to be in submicron level, which is far from highly efficient absorption of X-ray energy, further compromising the detection sensitivity. Here, we successfully demonstrate 3D hybrid perovskite crystal arrays with the thickness of ~300 μm on pixelated silicon substrate (forming co-axial silicon/perovskite heterojunction arrays) by melting PbBr2 and in situ chemical vapor conversion. Both morphological and optical properties of the resulting heterojunction arrays are systematically investigated. Furthermore, we demonstrate a high performance direct-conversion flat panel X-ray detector which exhibits high sensitivity of 242 μC Gyair−1 cm−2 that is much higher than the commercially available α-Se, and fast response speed (rising and falling time are 0.5 ms and 1.3 ms, respectively). The proposed strategy addresses the trade-off problem between the high sensitivity (requiring ~ mm-thickness perovskite crystal) and high spatial resolution (patterning of perovskite crystal) to achieve high-performance X-ray detection. This work not only offers a new pathway to fabricate pixelated μm-thick perovskite-based X-ray detectors, but also impacts on the application and functionalization of perovskite materials in silicon circuitry. [Display omitted] •The demonstration of high sensitivity (242 μC Gyair−1 cm−2) X-ray detector with fast response speed (~0.5 ms).•The demonstration of Si/perovskite detector for high-resolution X-ray imaging.•The addressing of the trade-off problem between the high sensitivity and high spatial resolution.•The demonstration of a new pathway (in situ synthesis) to fabricate pixelated μm-thick perovskite-based X-ray detectors.